Optical properties of bimetallic Au-Cu nanocrystals embedded in glass. (February 2018) - Zhang, Yijun; Jin, Yu; He, Meiling; Zhou, Lei; Xu, Tao; Yuan, Rongrong; Lin, Sai; Xiang, Weidong; Liang, Xiaojuan
Graphical abstract: Highlights: Bimetallic Au-Cu/Au-Cu sosoloid nanocrystals embedded in glass have been synthesized. We achieved good size control of the nanocrystals. The glasses with bimetallic nanoparticles exhibit enhanced for NLO. The mechanisms on the nonlinear effects of the obtained glasses are discussed. Abstract: Bimetallic gold-copper and gold-copper solid solutions nanocrystals (NCs) with orthorhombic morphologies were successfully embedded in sodium borosilicate glass; these materials were fabricated via a facile and synthetic sol-gel technique. Microstructural investigations demonstrate that the Au-Cu intermetallic nanostructure is generated in the glass host. Z-scan technique was applied to reveal the third-order nonlinear optical properties of the as-obtained glasses at the wavelength of 800 nm. The as-synthesized glasses exhibit similar nonlinear behaviors with reverse saturation absorption effects and self-focusing performances. The third-order nonlinear susceptibility χ (3) values were optimized by tuning the sizes of the Au-Cu NCs. The χ (3) of Au-Cu(1), Au-Cu(2) and Au-Cu(3) measured to be 3.1 × 10 −12, 5.4 × 10 −12, and 4.4 × 10 −12  esu for the single-pulse energy of 1 μJ. We have discussed the nonlinear optical mechanism of Au-Cu sodium borosilicate glass that may be due to the quantum confinement effects and surface plasmon resonance effects.